PERAN UNIT PELAKSANA TEKNIS PENDAPATAN DAERAH KECAMATAN MANDAU KABUPATEN BENGKALIS DALAM PEMUNGUTAN PAJAK HOTEL DI KECAMATAN MANDAU DITINJAU DARI PASAL 17 PERATURAN BUPATI KABUPATEN BENGKALIS NOMOR 17 TAHUN 2012 TENTANG PETUNJUK DAN PELAKSANAAN PAJAK HOTEL - Safutri, Siti Oktav Yanka; Firdaus, Emilda; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The taxation sector plays an important and strategic role in state revenue. Regional taxes are divided into two, namely provincial taxes and district/city taxes. In Bengkalis Regency, the hotel tax is regulated in the Bengkalis Regency Regent Regulation Number 17 of 2012 concerning Hotel Tax Instructions and Implementation. The purpose of writing this thesis: First, to determine the role of the UPT for the district of Mandau Bengkalis Regency in collecting hotel taxes. Second, to determine the inhibiting factors. Third, to find out the efforts that can be made by the UPT for the Mandau district of Bengkalis Regency in collecting hotel taxes.The type of research used is empirical or sociological legal research. Sources of data used in this study are primary data and secondary data. Data analysis is the process of compiling data so that the data can be interpreted. In this case, the analysis used is qualitative data analysis, namely data that cannot be measured or assessed with numbers directly. Thus, after the primary data and secondary data in the form of documents are obtained completely, then they are analyzed with regulations relating to the problem under study.From the results of research conducted that the role of the Regional Revenue Unit of Mandau District, Bengkalis Regency in collecting hotel taxes in terms of Article 17 of the Bengkalis Regency Regent Regulation No. 17 of 2012 concerning Instructions and Implementation of Hotel Taxes can be said to have not run optimally. This is because the work mechanism of the Regional Revenue Unit of Mandau District is not yet optimal as the executor and person in charge in the field of regional financial management and the lack of socialization of the application of Article 52 of the Bengkalis Regency Regional Regulation Number 11 of 2011 concerning Regional Taxes, namely hotel taxes to taxpayers. Keywords: Role – Supervision - Hotel Tax